Isoconversional Analysis of Corn Silk Thermal Decomposition Fitting Model by Pyrolysis Process - Himawan, Citrakara Upendra Sneha Bandhana Kusuma (TRANSMISI, 2022)
The pyrolysis characteristics and kinetics of corn silk were studied through thermogravimetric analysis in the normal room temperature range of -900 oC under a nitrogen atmosphere at heating rates of 20, 30 and 40 oC/minute. The results show that the pyrolysis process of corn silk is divided into three stages which can be associated with the process of dehydration or loss of water at a temperature of 65-150 oC, followed by a second stage, namely the main devolatilization at a temperature range of 225-525 oC and the final stage, namely slow decomposition up to 900 oC. The activation energy in the active pyrolysis stage was calculated using the Arrhenius fitting model and the isoconventional model using the Flynn-Wall Ozawa model and the Vyazovkin model. The resulting activation energies from the Arrhenius calculations are in the range of 195-215 kJ/mol and Ea using the Flynn-Wall Ozawa and Vyazovkin free model calculations of 195,355 and 215,522 kJ/mol, respectively.